2009
DOI: 10.1097/psy.0b013e3181acee12
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Practitioner Influences on the Placebo Effect in Irritable Bowel Syndrome

Abstract: Objective To determine whether placebo responses can be explained by characteristics of the patient, the practitioner, or their interpersonal interaction. Methods We performed an analysis of videotape and psychometric data from a clinical trial of IBS patients treated with placebo acupuncture in either a warm empathic interaction (Augmented, n=96), a neutral interaction (Limited, n=97), or a waitlist control (Waitlist, n=96). We examined the relations between placebo response and: (1) patient personality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(146 citation statements)
references
References 46 publications
6
137
1
2
Order By: Relevance
“…Furthermore, personality traits such as extraversion have been linked with placebo responses in patients diagnosed with irritable bowel syndrome, but only in the context of warm empathic interactions with the care provider (Kelley et al, 2009). These data suggest that personality variables interact with environmental (ie, social) cues to modulate behavioral and biological placebo responses.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, personality traits such as extraversion have been linked with placebo responses in patients diagnosed with irritable bowel syndrome, but only in the context of warm empathic interactions with the care provider (Kelley et al, 2009). These data suggest that personality variables interact with environmental (ie, social) cues to modulate behavioral and biological placebo responses.…”
Section: Introductionmentioning
confidence: 82%
“…In our data, this was reflected by positive correlations between agreeableness and m-opioid system activation in several midline regions (subgenual ACC, dorsal ACC and OFC) as well as the anterior and posterior insular cortex, NAc, amygdala and PAG. In this respect, agreeableness has also been linked to greater effectiveness of placebo acupuncture (Kelley et al, 2009) and empathic traits to placebo analgesia mediated through social learning (Colloca and Benedetti, 2009). Moreover, reciprocal altruism has been related to resilience (Charney, 2004) and the activation of brain areas linked to reward processing (Rilling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The placebo, a cool-blue tinted hand disinfectant with no anesthetic properties, was then applied on both volar forearms. In order to facilitate acceptance of the analgesia suggestion, the placebo treatment administration was delivered in a warm, trustful, encouraging and caring manner since it has been shown that a good relationship between health provider and patient plays an important role in shaping the placebo response (39,40).…”
Section: Expectation Induction and Placebo Administrationmentioning
confidence: 99%
“…Although age appears to be a relevant moderator of the placebo response (as discussed above), gender differences in adults were occasionally investigated, but results are generally not consistent (5,50,51). However, experimental studies on placebo analgesia usually reveal higher placebo response rates in male adults (52).…”
Section: Are the Mediators And Moderators Of The Placebo Effect Similmentioning
confidence: 99%
“…One of the rare experimental studies in children and adolescents also revealed effects of verbal instructions on needle pain from venipuncture (76). Furthermore, warm empathic interactions between practitioners and patients have been shown to evoke significant placebo effects in adult patients with irritable bowel syndrome (50). Therefore, the effects of expectations and of patient-practitioner interactions on symptoms in children and adolescents, as well as their mediation by parents, should be further investigated.…”
Section: What Are the Consequences For Clinical And Experimental Studmentioning
confidence: 99%